Spin cluster size dependence of exchange bias effect in Mn50Ni40Ga10 Heusler alloys. (April 2019) - Zhang, Yin; Li, Jianing; Tian, Fanghua; Cao, Kaiyan; Wang, Dingchen; Ren, Shuai; Zhou, Chao; Yang, Sen; Song, Xiaoping
Abstract: The technique based on exchange bias effect is believed to play a significant role in next-generation spin-involved magnetic devices. However, 60 years after the discovery of the exchange bias, it remains unclear about origin and influencing factors of exchange bias. In this study, a giant exchange bias field of 5132 Oe was introduced in Mn50 Ni40 Ga10 Heusler alloys at 2 K with a cooling field of 10 kOe. Magnetic measurements showed that the giant exchange bias effect at lower temperature originates from the coupling between super spin glass and antiferromagnetic matrix. Different from previous reports, we elaborated on the issue of cooling field dependence from the perspective of size effect. The size effect was further demonstrated by calculating and comparing the relaxation time of super spin glass under different cooling fields. Although the relationship between particles sizes and relaxation time yet requires further validation, the current proposal can be applied to most exchange bias in Heusler systems. Highlights: A giant exchange bias field of 5132 Oe was introduced in Mn50 Ni40 Ga10 Heusler alloys at 2 K with a cooling field of 10 kOe. The exchange bias is attributed to the exchange coupling between super spin glass and antiferromagnetic matrix. It is found that the relaxation timeτ 0 will change depending on the cooling field. A size effect was proposed to interpret the dependence of exchange bias effect on cooling field.